SOCIAL LONELINESS AS A FACTOR OF TRANSFORMATION OF THE COMMUNICATION SITUATION IN THE CONDITIONS OF THE CORONAVIRUS PANDEMIC - Никитин, Александр; Горюнова, Анна; Савруцкая, Елизавета; Устинкин, Сергей (SWorldJournal, 2022)
The paper discusses the problems of the formation of a new type of social loneliness associated with the transformation of the modern communicative situation developing under the influence of the coronavirus pandemic. The purpose of the study is to prove